2020
DOI: 10.21203/rs.2.19108/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of China’s 2009 healthcare reform on the utilisation of continuum of care for maternal health services: Evidence from two cross-sectional household surveys in Shaanxi Province

Abstract: Background: Continuum of care for maternal health services (CMHS) is a proven approach to improve health and safety for mothers and newborns. This study aims to explore the influence of China’s 2009 healthcare reform on improving the CMHS utilisation. Methods: This population-based cross-sectional quantitative study included 2332 women drawn from the fourth and fifth National Health Service Surveys of Shaanxi Province, conducted in 2008 and 2013 respectively, before and after China’s 2009 healthcare reform. A … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The results of this study were lower than those of studies conducted in Egypt (50.4%) and Cambodia (60%) respectively [25,28]. The differences might be explained by variation in geographic location, settings, access to health facilities, outcome ascertainment and eligibility criteria used.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The results of this study were lower than those of studies conducted in Egypt (50.4%) and Cambodia (60%) respectively [25,28]. The differences might be explained by variation in geographic location, settings, access to health facilities, outcome ascertainment and eligibility criteria used.…”
Section: Discussioncontrasting
confidence: 88%
“…In this study, educated women had a better chance of receiving a complete continuum of maternity care than women with no formal education. Studies in Debre Berhan, South Asia and Sub-Saharan Africa, Pakistan, Cambodia, and Nepal backed with this conclusion [2,15,25,27]. This could be explained by the fact that education can improve women's understanding, access to information, and capacity to grasp information about healthcare services from the media and healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the portion of the low-income population that is unemployed or informally employed bears more of the burden of health care costs, which clearly results in inequity in the distribution of medical resources due to inequitable health insurance [30][31][32]. Moreover, some studies have found that the type of the health insurance affects equity in the use of health care services, such that the use of health care services differs among residents covered by different insurance policies [33][34][35][36].…”
Section: Establish a Unified Health Insurance Systemmentioning
confidence: 99%